The Development of a Six Sigma–Based Ulcus Decubitus Prevention Model to Respond to Adverse Events - Martini Sriwulaningdyah; Erna Dwi Wahyuni (Universitas Airlangga, 2017)
Introduction: Based on the number of incidences of Ulcus Decubitus in 2015 which was 2.4 ‰ and 1.59 ‰ in 2016, the incidences of Ulcus Decubitus is an indicator of patient safety. In one of the public hospitals in Surabaya, it showed that the achievement of a Ulcus Decubitus indicator had not been reached yet (the standard is 1.5 ‰ per year). One of the efforts that can be done to prevent the occurrence of ulcus decubitus is by way of Six Sigma-based ulcus decubitus prevention.Methods: The design of this research was an explanatory research study using a cross-sectional approach. The research respondents were nurses at Inpatient Wards (4 Rooms); 57 nurses via the Purposive Sampling technique. The research data was analysed with Partial Least Square (PLS)Results: Individual factors (Path Coefficient 0,200 t: 6,580), organisational factors (Path Coefficient 0,373 t: 9,278) and management factors (Path Coefficient 0.099 t: 2.184) are all significantly correlated with the Six Sigma-based Ulcus decubitus prevention.Conclusions: Individual, Organisational and Management factors are important factors in the Six Sigma-based Ulcus Decubitus prevention model. It needs advanced research to find out how much the influence of Six Sigma-based Ulcus Decubitus prevention implementation will decrease the incidences of Ulcus Decubitus.